Níveis nutricionais de metionina+cistina digestível para poedeiras semipesadas - Polese, Clauber (2011)
With the objective of determining the requirement of digestible methionine+cystine for laying hens from 50 to 66 weeks of age and 75 to 90, two experiments were accomplished at the Center for Experimental Stations of Paraná Federal Technological University, Campus Dois Vizinhos. One hundred and fifty Shaver Brown hens were used in a completely randomized design, distributed in five treatments, six replicates and five birds per experimental unit. The hens were fed a basal diet containing 2,850 kcalME/kg, 16% CP supplemented with 0.132, 0.174, 0.215, 0.256 and 0.298% of DL-methionine (99%), in order to provide tested levels of 0.572, 0.613, 0.653, 0.693 and 0.734% of digestible methionine+cystine. From 75 to 91 weeks of age levels of 0.588, 0.628, 0.669, 0.709 and 0.750% of digestible methionine+cystine were tested. The following parameters were evaluated: feed intake, digestible methionine+cystine intake, feed conversion/dozen eggs, feed conversion/egg mass, egg weight, egg mass, percentage of egg components (yolk, shell, albumen, shell weight and shell weight per unit of area surface), internal egg quality (Haugh unit, yolk index and albumen index) and specific gravity. In experiment 1, the levels of digestible methionine+cystine did not affect feed intake, production, egg mass, specific gravity and internal egg quality, except the percentage of yolk and albumen, which showed linear increase in yolk percentage and linear decrease in the percentage of albumen. The lowest level of methionine+cystine (0.572%) gave better feed conversion (kg/dz) corresponding to 682mg of methionine+cystine/hen/day. In experiment 2, there was no effect of methionine+cystine levels on productive parameters, performance and egg quality. The level of 0.588% digestible methionine+cystine, corresponding to 634.73 mg, supplied the daily needs of birds from 75 to 91 weeks of age